Cybermedia : explorations in science, sound, and vision - Vernallis, Carol; Rogers, Holly (Professor of music); Kara, Selmin; Leal, Jonathan, 1989- (New York, NY, USA ; London, UK : Bloomsbury Academic, 2022)
"We're experiencing a time when digital technologies and advances in artificial intelligence, robotics, and big data are redefining what it means to be human. How do these advancements affect contemporary media and music? This collection traces how media, with a focus on sound and image, engages with these new technologies. It bridges the gap between science and the humanities by pairing humanists' close readings of contemporary media with scientists' discussions of the science and math that inform them. This text includes contributions by established and emerging scholars performing across-the-aisle research on new technologies, exploring topics such as facial and gait recognition; EEG and audiovisual materials; surveillance; and sound and images in relation to questions of sexual identity, race, ethnicity, disability, and class and includes examples from a range of films and TV shows including Blade Runner, Black Mirror, Mr. Robot, Morgan, Ex Machina, and Westworld. Through a variety of critical, theoretical, proprioceptive, and speculative lenses, the collection facilitates interdisciplinary thinking and collaboration and provides readers with ways of responding to these new technologies."--
Part one: AI and robotics. Could the AI of our dreams ever become reality? / James L. McClelland -- Director Alex Garland converses with Cybermedia's scientists and media scholars / Jonathan Leal and Carol Vernallis -- (S)Ex machina and the Cartesian theater of the absurd / Simon D. Levy and Charles W. Lowney -- Epiphany, infinity and transcendent AI / Zachary Mason -- Part two: Big data, sentience, and the universe. A MASSIVE swirl of pixels : Radiohead's "Go to sleep" / Steen Ledet Christiansen -- The rise of the machine : body-knowing, neural nets, and emergent freedom / Charles W. Lowney -- The quantum computer : sci-fi narrative's favorite character / Leonardo P.G. De Assis -- Composer Ben Salisbury discusses scoring science for Alex Garland / Ben Salisbury, Holly Rogers, John McGrath, Carol Vernallis, and Dale Chapman -- Ex machina and the question of consciousness / Murray Shanahan -- Part three: The neuroscience of affect and event perception. "A solid popularity arc" : affective economies in Black mirror's "Nosedive" / Dale Chapman -- Cognitive boundaries, "Nosedive," and Under the skin : interview with Jeffrey Zacks / Carol Vernallis, Jonathan Leal, and Dale Chapman -- Toward an AI future of comics study and creation : a cognitive-affective approach / Frederick Luis Aldama and Laura Wagner -- Part four: The digital west. The philosophy of Westworld / Paul Skokowski -- New visions of the old West : AI, self, and other in Westworld / Christopher Minz -- Scoring music for Westworld : then and now : a cognitive perspective / Annabel J. Cohen -- Part five: Interface, desire, collectivity. Director Terence Nance discusses Random acts of flyness / Carol Vernallis, Jonathan Leal, Holly Rogers, Elizabeth Reich and the contributors of Cybermedia -- The gift of Black sonics : interface and ontology in Sorry to bother you and Random acts of flyness / Elizabeth Reich -- Technology, chaos, and the nimble subversion of Random acts of flyness / Eric Lyon -- Expecting the twist : how media navigate the intersections among multiple sources of prior knowledge / Noah Fram -- Face color / Bevil R. Conway -- Part six: Productive neuropathologies. Digital vitalism / Marta Figlerowicz -- Neuroplasticity : from experience to healing / Sara Ferrando Colomer -- Where is my mind? : Mr. Robot and the digital neuropolis Patricia Pisters -- The dopamine circuits of wanting, liking, habits and goals : an interview about Mr. Robot with neuroscientist Talia Lerner / Jonathan Leal, Carol Vernallis and Patricia Pisters -- The taste of cybermedia : an interview with Hojoon Lee, the Lee Lab at Northwestern University / Julia Peres Guimarães, Selmin Kara, and Carol Vernallis.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central platform, viewed March 8, 2022).
eBooks on EBSCOhost
Keywords: Mass media and technology; Digital media; Music -- Technological innovations; Mass media -- Technological innovations; Music and technology; Music & Sound Studies; Music and Media (Music); New Media and Technology (Film & Media); Digital Art and Media (Film & Media); Médias et technologie; Médias numériques.; Musique -- Innovations; Médias -- Innovations; Musique et technologie; Music recording & reproduction; Music industry; Impact of science & technology on society; Media studies; Music -- History & Criticism; Technology & Engineering -- Social Aspects; Digital media; Mass media and technology; Mass media -- Technological innovations; Music and technology; Music -- Technological innovations